Answer :

Given: (2a - 1)x + 3y = 5 – eq 1

3x + (b - 1)y = 2 – eq 2

Here,

a_{1} = (2a - 1), b_{1} = 3, c_{1} = - 5

a_{2} = 3 , b_{2} = (b - 1), c_{2} = - 2

Given that system of equations has infinitely many solution

∴ = =

= =

Here,

=

- 2×(2a - 1) = 3×( - 5)

- 4a + 2 = - 15

- 4a = - 15 - 2

- 4a = - 17

b =

∴ b = -

Also,

=

3( - 2) = - 5×(b - 1)

- 6 = - 5b + 5

5b = 5 + 6

5b = 11

b =

∴b =

∴ a = , b =

Rate this question :

How useful is this solution?

We strive to provide quality solutions. Please rate us to serve you better.

Related Videos

Two Stories about Flying39 mins

Resistors in Parallel39 mins

Resistors in Series47 mins

Transportation in One Shot42 mins

Resistors in Series42 mins

Human Reproduction in One Shot45 mins

Extraction of Metal56 mins

Outcomes of Democracy43 mins

Refraction of Light-241 mins

Reflection of light-238 mins

Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Expertsview all courses

Dedicated counsellor for each student

24X7 Doubt Resolution

Daily Report Card

Detailed Performance Evaluation